What does scientometry tell us about mercury toxicology and its biological impairments? - Baia-da-Silva, Daiane Claydes; Mendes, Paulo Fernando Santos; Silva, Diane Cleydes Baia da; Chemelo, Victória Santos; Bittencourt, Leonardo Oliveira; Padilha, Pedro Magalhães [UNESP]; Oriá, Reinaldo Barreto; Aschner, Michael; Lima, Rafael Rodrigues (Elsevier, 2024)
Mercury is a toxic pollutant that poses risks to both human and environmental health, making it a pressing public health concern. This study aimed to summarize the knowledge on mercury toxicology and the biological impairments caused by exposure to mercury in experimental studies and/or diagnosis in humans. The research was conducted on the main collection of Web of Science, employing as a methodological tool a bibliometric analysis. The selected articles were analyzed, and extracted data such as publication year, journal, author, title, number of citations, corresponding author's country, keywords, and the knowledge mapping was performed about the type of study, chemical form of mercury, exposure period, origin of exposure, tissue/fluid of exposure measurement, mercury concentration, evaluation period (age), mercury effect, model experiments, dose, exposure pathway, and time of exposure. The selected articles were published between 1965 and 2021, with Clarkson TW being the most cited author who has also published the most articles. A total of 38% of the publications were from the USA. These studies assessed the prenatal and postnatal effects of mercury, emphasizing the impact of methylmercury on neurodevelopment, including motor and cognitive evaluations, the association between mercury and autism, and an evaluation of its protective effects against mercury toxicity. In observational studies, the blood, umbilical cord, and hair were the most frequently used for measuring mercury levels. Our data analysis reveals that mercury neurotoxicology has been extensively explored, but the association among the outcomes evaluated in experimental studies has yet to be strengthened. Providing metric evidence on what is unexplored allows for new studies that may help governmental and non-governmental organizations develop guidelines and policies.
Keywords: Bibliometric analysis; Health; Mercuric dichloride; Mercury; Methylmercury; Neurotoxicology